PENGELOLAAN BARANG MILIK DAERAH (BMD) KABUPATEN ROKAN HILIR (STUDI KASUS KOMPLEKS PERKANTORAN KAWASAN BATU ENAM) - Mutia Mariam; Zulkarnaini Zulkarnaini (Universitas Tribhuwana Tungga Dewi, 2021)
This study aims to determine: (1) Management of Regional Property (BMD) of Rokan Hilir Regency, especially the management of buildings and buildings belonging to the regional government in the Batu Six office complex (2) Inhibiting Factors in the Management of Regional Property of Rokan Hilir Regency. In this study, the researcher uses the theory of (Hindawan, et al 2006:119) in which the asset life cycle has four phases, namely planning, procurement, operation and disposal. The findings in this study are that there are still many local government buildings that have stopped being activated, causing several buildings and buildings to be abandoned, starting from buildings that are still fit for use to buildings whose physical condition is no longer usable. From another phenomenon, researchers see that there is still less emphasis on local government policies in procuring regional property. The inhibiting factors in the management of regional property are the lack of quality human resources and the lack of emphasis on the government in implementing regional regulations, resulting in a lack of optimization of the management of Regional Property by the regional government.Keywords: Management; Regional Property Penelitian ini bertujuan untuk mengetahui : (1) Pengelolaan Barang Milik Daerah (BMD) Kabupaten Rokan Hilir khususnya pengelolaan pada gedung dan bangunan milik pemerintah daerah di kompleks perkantoran kawasan batu enam (2) Faktor Penghambat Pengelolaan Barang Milik Daerah Kabupaten Rokan Hilir. Dalam penelitian ini peneliti menggunakan teori (Hindawan, dkk 2006:119) yang mana siklus hidup asset memiliki empat fase yaitu perencanaan, pengadaan, pengoperasian dan penghapusan. Temuan pada penelitian ini adalah masih banyaknya bangunan pemerintah daerah yang berhenti difungsikan sehingga menyebabkan beberapa gedung dan bangunan terbengkalai, dimulai dari bangunan yang masih layak pakai hingga bangunan yang kondisi fisiknya sudah tidak dapat digunakan. Dari fenomena lain peneliti melihat masih kurang tegasnya pemerintah daerah dalam pemberlakuan kebijakan dalam melakukan pengadaan barang milik daerah. Faktor-faktor penghambat dalam pengelolaan barang milik daerah tersebut ialah kurangnya kualitas sumber daya manusia dan tidak tegasnya pemerintah dalam menjalankan peraturan daerah, sehingga mengakibatkan kurangnya pengoptimalisasian pengelolaan Barang Milik Daerah oleh pemerintah daerah.Kata Kunci: Pengelolaan; Barang Milik Daerah